Flexible Pavement Design Criterion Based on Octahedral Shear Stresses - Lazăr Ştefan Marian; Răcănel Carmen (Romanian Journal of Transport Infrastructure, 2017)
The judicious pavement design is the key factor in achieving the longest service life and the lowest maintenance and rehabilitation costs. It is based on the consideration of the phenomena in which the pavement structures are subjected to exploitation and the limitation of their destructive effects.